Enhancing Human Development Quality in Indonesia: Socio-Economic and Technological Capabilities - Ika Yuli Setyowati; Nazaruddin Malik; Muhammad Sri Wahyudi Suliswanto (Faculty of Economic and Business, 2024)
Research Originality: Human development is a complex issue faced by various countries worldwide. Technology is considered to have the potential to significantly impact the landscape of human development due to its potential for penetration. This research contributes to the development literature in Indonesia by focusing on the important aspects of the influence of socio-economic factors and technological capabilities on the quality of human development.Research Objectives: This research aims to analyse how socio-economic and technological capabilities influence the quality of human development in Indonesia.Research Methods: Using panel data from 34 provinces spanning the period from 2015 to 2022, the research employs a Panel Data Regression Analysis model with the best-fitted Fixed Effect model.Empirical Results: The results of this study indicate that socio-economic factors, as seen through unemployment and poverty, significantly negatively impact Indonesia's Human Development Index (HDI). Economic growth has an insignificant effect on Indonesia's HDI. Technological capabilities, measured through the ICT Development Index, and the proportion of adolescents and adults aged 15-59 with ICT skills, have a significantly positive impact on Indonesia's HDI.Implications: The results of this research identify factors that can either encourage or hinder HDI, offering valuable insights for government policymakers to enhance HDI in Indonesia, particularly in each region.JEL Classification: O15, O30, O47How to Cite:Setyowati, I. Y., Malik, N., & Suliswanto, M.S.W. (2024). Enhancing Human Development Quality in Indonesia: Socio-Economic and Technological Capabilities. Etikonomi, 23(1), 93 – 108. https://doi.org/10.15408/etk.v23i1.35508.